Fiscal Discipline in WAEMU : Rules, Institutions, and Markets - Hitaj, Ermal (IMF Working Papers; Working Paper, 2013)
This paper gauges the scope for market discipline and the effectiveness of the regional surveillance framework in the West African Economic and Monetary Union (WAEMU). The paper finds that the responsiveness of sovereign bond rates to governments' fiscal behavior in the regional financial market remains limited. In addition, the paper examines the effectiveness of fiscal rules and institutions in an environment where financial markets fall short of exerting a significant disciplining effect on governments.